Optimization of coconut biodiesel and glycerol yield at minimum production time a goal programming approach - Maranga, Joey Villacura (2005)
This study aims to optimize the production of coconut biodiesel and glycerol at minimum setting time. The experimental data consisted of the inputs (coconut oil, catalyst concentrations and the amounts of methanol), setting time, and outputs (glycerol and CMF) at 320C transesterification. The response surfaces were then the aid of MATHEMATICA Version 5 Software. These response surfaces were then produce 90% CME and glycerol at 320 C and 650 C. the results of the Response Surface Modeling showed that the shape of the graph of CME equations at 320C and 650C was concave while that of glycerol was convex. The settling time equation for the 320C was convex while the other time equation for the 650C was an almost plane. Results of the goal programming at 320C transesterification after five minutes settling time showed that 98.98 g of CME can be produce from 100 g of coconut oil, 0.3930 g of NaOH and 30.1838 g of methanol. Also, 100 g of coconut oil, 0.9906 g of NaOH and 2.1856 g of methanol could produce 78.28 g of glycerol. On the other hand, transesterification at 650C revealed that 111.51 g of CME could be produced from 100 g of coconut oil, 0.5026 g of NaOH and 32 g of methanol after 16.2294 min settling time. Finally, 19.55 g of glycerol can be extracted from 100 g of coconut oil, o.3278 g of NaOH and 31.698 g of glycerol can be extracted 100 g of coconut oil, 0.3278 g of NaOH and 31. 698 g of methanol after five min settling time